Pathophysiological role of guanylate-binding proteins in gastrointestinal diseases - Britzen-Laurent, Nathalie; Herrmann, Christian; Naschberger, Elisabeth; Croner, Roland S.; Stürzl, Michael (World Journal of Gastroenterology, 2016)
Guanylate-binding proteins (GBPs) are interferon-stimulated factors involved in the defense against cellular pathogens and inflammation. These proteins, particularly GBP-1, the most prominent member of the family, have been established as reliable markers of interferon-?-activated cells in various diseases, including colorectal carcinoma (CRC) and inflammatory bowel diseases (IBDs). In CRC, GBP-1 expression is associated with a Th1-dominated angiostatic micromilieu and is correlated with a better outcome. Inhibition of tumor growth by GBP-1 is the result of its strong anti-angiogenic activity as well as its direct anti-tumorigenic effect on tumor cells. In IBD, GBP-1 mediates the anti-proliferative effects of interferon-? on intestinal epithelial cells. In addition, it plays a protective role on the mucosa by preventing cell apoptosis, by inhibiting angiogenesis and by regulating the T-cell receptor signaling. These functions rely to a large extent on the ability of GBP-1 to interact with and remodel the actin cytoskeleton.
EVALuna2:15238